Study on Development Risk of Overseas Transportation Infrastructure under the New Form Based on Interpretive Structure Model - Liang Ou; Chongsen Ma; Yun Chen; Jing Zhang (Advances in Civil Engineering)
With the improvement of China’s comprehensive national strength, more and more construction enterprises began to undertake overseas construction projects. Under the premise of the epidemic situation and the increasingly severe international situation, it is of great significance to study the risk control of overseas transportation infrastructure construction. This paper constructs the risk influencing factor model of overseas transportation infrastructure development risk in the new form from six aspects, that is, decision-making risk, design and planning risk, construction risk, operation risk, government risk, and force majeure, and uses the interpretative structure model and fuzzy comprehensive evaluation method. The key factors affecting the risk of overseas transportation foundation design and development are studied, and the adaptive solutions are put forward.